Flourishing as a Predictor of Quality of Life among University Students - Ghania Nurbayani Fadlillah; Gian Sugiana Sugara; Anandha Putri Rahimsyah (POTENSI : Journal of Education and Human Development, 2025)
Flourishing and quality of life are two important indicators of positive mental health that determine students’ ability to adapt to academic demands and psychosocial development. This study aims to analyze the relationship between flourishing and quality of life among university students. Using a quantitative cross-sectional design with a correlational approach, the study involved 660 students from three universities and measured flourishing and quality of life using standardized instruments. The analysis results show that flourishing has a significant positive relationship with quality of life (r = 0.616), with dimensions such as meaning, relationships, and accomplishment contributing the most to various QoL domains. These findings emphasize that the higher the level of flourishing among students, the better their perceived quality of life. Overall, the study highlights the urgency of developing positive psychology–based programs to enhance student well-being in higher education settings.